Edukasi Kesehatan dengan Audiovisual tentang Pencegahan Stunting pada Ibu Balita di Poli Anak RS Bhayangkara Brimob Depok - Norma Widiyaningrum; Yulia Agustina (Universitas Malahayati Lampung, 2024)
ABSTRACT Toddlers can be defined as an individual or group of individuals from a population within a certain age range. According to the division of age groups, toddlers can be divided into 2 groups, namely toddlers (ages 1-3 years) and pre-school (ages 3-6 years). Children under five years old are a group that shows rapid body growth but the content group is the most common group that suffers from malnutrition. Stunting is a condition where children experience growth disorders, so that their height is not in accordance with their age, as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. The problem of stunting is a public health problem associated with an increased risk of morbidity, mortality and obstacles to growth both motor and mental so that comprehensive monitoring and prevention measures are needed. Providing education with audiovisual methods as a means for mothers of toddlers so that they can improve their ability to prevent stunting in the pediatric clinic of Bhayangkara Brimob Hospital. Using 30 samples of mothers of toddlers with Pre - Experimental design with the research design used is pre-test and post - test. it was found that there was an increase in the average attitude score before being given education about stunting, namely 9.7 and after being given education about stunting, namely 24.8. The results of the interpretation of the Paired Sample T-test pre-test and post-test test of respondents based on pair 1 output obtained a Sig value. (2-tailed) of 0.001 0.005. Conclusions and Health education using audiovisuals affects the knowledge of mothers of toddlers about preventing stunting in children. It is hoped that it can be a reference for health workers in hospitals in providing health promotion to increase mothers' knowledge and attitudes about preventing stunting using effective media so that early detection of stunting can be done. Keywords: Audiovisual, Health Education, Mothers of Toddlers, Stunting Prevention ABSTRAK Balita dapat diartikan sebagai individu atau sekelompok individu dari suatu penduduk dalam rentang usia tertentu. Menurut pembagian kelompok umur balita dapat dibagi menjadi 2 kelompok yaitu batita (usia 1-3 tahun) dan pra sekolah (usia 3-6 tahun). Anak dibawah lima tahun merupakan kelompok yang menunjukkan pertumbuhan badan yang pesat namun kelompok isi merupakan kelompok tersering yang menderita kekurangan gizi. Stunting adalah suatu kondisi dimana anak mengalami gangguan pertumbuhan, sehingga tinggi badan anak tidak sesuai dengan usianya, sebagai akibat dari masalah gizi kronis yaitu kekurangan asupan gizi dalam waktu yang lama. Masalah stunting merupakan masalah kesehatan masyarakat yang berhubungan dengan meningkatnya risiko kesakitan, kematian dan hambatan pada pertumbuhan baik motorik maupun mental sehingga perlunya tindakan pengawasan dan pencegahan secara komperhensif. Memberikan edukasi dengan metode audiovisual sebagai sarana bagi ibu balita sehingga dapat meningkatkan kemampuan dalam pencegahan stunting di poli anak Rumah Sakit Bhayangkara Brimob. Menggunakan 30 sample ibu balita dengan design Pre – Experimental dengan rancangan penelitian yang digunakan yaitu pre-test dan post – test. didapatkan hasil terdapat peningkatan rerata skor sikap sebelum diberikan edukasi tentang stunting yaitu 9,7 dan setelah diberikan edukasi tentang stunting yaitu 24,8. Hasil interpretasi Uji Paired Sample T-test pre-test dan post-test responden berdasarkan output pair 1 diperoleh nilai Sig. (2-tailed) sebesar 0,001 0,005. Edukasi kesehatan dengan menggunakan audiovisual berpengaruh terhadap pengetahuan ibu balita tentang pencegahan stunting pada anak. Diharapkan dapat menjadi acuan bagi tenaga kesehatan di Rumah Sakit dalam memberikan promosi kesehatan untuk meningkatkan pengetahuan dan sikap ibu tentang pencegahan stunting menggunakan media yang efektif sehingga bisa dilakukan deteksi dini mengenai stunting. Kata Kunci: Audiovisual, Edukasi Kesehatan, Ibu Balita, Pencegahan Stunting